Brain response in asthma: the role of “lung-brain” axis mediated by neuroimmune crosstalk - Wang, Yao; Mou, Ya-Kui; Wang, Han-Rui; Song, Xiao-Yu; Wei, Shi-Zhuang; Ren, Chao; Song, Xi-Cheng (Frontiers in Immunology, 2023)
In addition to typical respiratory symptoms, patients with asthma are frequently accompanied by cognitive decline, mood disorders (anxiety and depression), sleep disorders, olfactory disorders, and other brain response manifestations, all of which worsen asthma symptoms, form a vicious cycle, and exacerbate the burden on families and society. Therefore, studying the mechanism of neurological symptoms in patients with asthma is necessary to identify the appropriate preventative and therapeutic measures. In order to provide a comprehensive reference for related research, we compiled the pertinent literature, systematically summarized the latest research progress of asthma and its brain response, and attempted to reveal the possible “lung–brain” crosstalk mechanism and treatment methods at the onset of asthma, which will promote more related research to provide asthmatic patients with neurological symptoms new hope.